Pelatihan Sertifikasi Halal sebagai Upaya Menunjang Ketahanan Ekonomi Kelompok Wanita Pesisir (KWP) Pantai Kukup Yogyakarta - Nur Aini; Rohmat Dwi Yunianta (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
This article aims to describe the finding of community engagement of IIQ An Nur in the coastal women's group (KWP) Kukup Beach Yogyakarta in order to that they have economic resilience through halal certification training. Economic resilience for coastal communities has become a necessity, not just a wish. This is because the life of the coastal community depends on the economic life of the coastal potential and its development. For this reason, it is necessary to provide assistance to coastal communities in developing their environmental potential as well as training in packaging product and halal certification and subsequently they have products with high economic value. The method used in this community engagement is the PRA (participatory rural appraisal) method. The results of the community engagement show that through assistance with financial literacy, product packaging and halal certification, the amount of production and profits for the company can be increased and the marketing reach can be expanded. Apart from that, from the consumer side, there is a feeling of security and stability because the packaging for KWP Pantai Kukup Yogyakarta products looks more attractive and is halal certified.